The Stimulant Selective Severity Assessment: A replication and exploratory extension of the Cocaine Selective Severity Assessment. (23rd February 2019) - Walker, Robrina; Northrup, Thomas F.; Tillitski, John; Bernstein, Ira; Greer, Tracy L.; Trivedi, Madhukar H.
Abstract: Background : Cocaine and methamphetamine have similar withdrawal symptoms and many individuals concurrently use both substances; however, no measures concurrently assess withdrawal from multiple stimulants. Objectives : This study's aim was to explore the Stimulant Selective Severity Assessment (SSSA), a modified version of the Cocaine Selective Severity Assessment (CSSA), in a sample of stimulant users to determine if it can assess withdrawal symptoms in users of one or more stimulants. Methods : Baseline data were analyzed from the STimulant Reduction Intervention using Dosed Exercise trial, a multisite randomized clinical trial that evaluated exercise versus health education on drug use outcomes in individuals with stimulant use disorders. Data were analyzed for internal consistency, construct validity, and scale dimensionality. Results : Internal consistency for the full sample was good ( α  = 0.81; N  = 302), with similar alphas in Cocaine (0.81; n  = 177) and Cocaine/Other Stimulant (0.82; n  = 92) groups, but with much lower alpha for the group without cocaine use (Other Stimulant, i.e., primarily methamphetamine, α  = 0.66; n  = 32). Support for construct validity was evidenced by significant positive correlations ( r  = 0.17 to 0.67) with measures of stimulant craving, depressive symptoms, and pain. Four factors were revealed. Conclusions/Importance : The Stimulant Selective Severity Assessment is a new measure that can be used to assess withdrawal symptoms in users of cocaine or cocaine plus methamphetamine, but it should not be administered to users of methamphetamine only. Trial registration: ClinicalTrials.gov identifier: NCT01141608.